Wakaf dalam Pemberdayaan Umat - Muhammad Al Faruq (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
In Islamic history, waqf is one of the Islamic economic institutions that played an important role in the economic empowerment of the people. Waqf plays a role in empowering not only in the field of economics but also in the fields of social, education and health. So the role of waqf for the economy is very important and with professional management will certainly make waqf more productive. The empowerment of waqf has been proven in some Islamic countries such as Bangladesh where with waqf funds can support the economy of both the rich and the poor. If in Indonesia, more productive waqf funds will increase Indonesia's economy.